2016
DOI: 10.15405/epsbs.2016.09.43
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Perceptions of Turkish EFL Instructors in Relation to Their Students

Abstract: Problem Statement: Despite the fact that the metaphorical perceptions of university instructors about their students are important in teacher-student interactions in the classroom environment, as they pave the way to an effective teaching-learning process, in Turkey there are a limited number of studies on them. Purpose of the Study: The purpose of this study is to determine the metaphorical perceptions of Turkish EFL Instructors in relation to their students. Method: In this study both qualitative and quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Şahin, Seçer & Erişen, 2016), EFL learners (e.g. Elkılıç & Aybirdi, 2016) and learning environment (e.g. İnceçay, 2015), and ELT coursebooks (e.g.…”
Section: Criteria For Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Şahin, Seçer & Erişen, 2016), EFL learners (e.g. Elkılıç & Aybirdi, 2016) and learning environment (e.g. İnceçay, 2015), and ELT coursebooks (e.g.…”
Section: Criteria For Study Selectionmentioning
confidence: 99%
“…Given all these virtues available, teachers' roles through the analysis of metaphors have been revealed in a plethora of studies with the inclusion of students, pre-service teachers and teachers themselves with regard to different subjects (Fleener, 1995;Saban et al, 2006;Seferoğlu, Korkmazgil & Ölçü, 2009;Sumsion, 2003;Hamilton, 2016). Likewise, in foreign language learning and teaching field too, metaphors have amply been used to elicit metaphors about EFL learners, learning and teaching (Şimşek, 2014;Erkmen, 2010;Fang, 2015;Coşkun, 2015;Elkılıç & Aybirdi, 2016;Özcan, Koçyiğit & Erdem, 2017), language learning process (Baş & Gezegin, 2015), foreign language classroom (İnceçay, 2015), ELT coursebooks (Kesen, 2010;ALLS 9(2):65-76 Şimşek & Dündar, 2015), speaking English (Dinçer, 2017), and most commonly about EFL teachers (Wan, Low & Li, 2011;Nikitina & Furuoka, 2008;Akbari, 2013;Oktay & Osam, 2013;Jitpranee, 2017;Tercan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…L2 learners may not be aware of the fact that L2 sentences are punctuated differently than those in their first language (L1). For example, in writing samples of Turkish-L1 learners of English, the impact of mother-tongue interference was apparent as students, particularly lower-level ones, usually used the rules in their L1 to punctuate L2 writing (Elkılıç, Han & Aydın, 2009; Kırkgöz, 2010). Similarly, another corpus study of undergraduate Turkish-L1 learners’ writing concluded that the punctuation errors may be caused by L1 transfer or complexity of the connectives in English (Altunay, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There have been different studies in relation to metaphors about students, teachers, lessons, languages as well as school environments [6,12,13,14,15,16,17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In their study Elkılıç and Bayrakcı [21] on the metaphorical perceptions of 68 Turkish students in the Department of Translation and Interpretation, Faculty of Science and Letters at Kafkas University, Turkey in relation to their instructors and determined 60 valid metaphors for English language instructors and 58 for French language instructors, and grouped them under 7 conceptual categories .…”
Section: Introductionmentioning
confidence: 99%